Clinical assessment and crisis intervention for the suicidal bipolar disorder patient. - Saunders, K; Hawton, K (2013)
OBJECTIVE: Suicidal behaviour is common in people suffering with bipolar disorder, and suicide is a leading cause of death in this group. Our aim in this review is to provide an overview of key assessment and management strategies, highlight research findings relevant to suicide prevention, and identify important areas for future research. METHODS: We reviewed the published literature regarding the risk factors for and management of suicidał behaviour in individuals with bipolar disorder using the Pubmed and PsychINFO databases. Where available, we focused our search on systematic reviews. RESULTS: Suicide is usually associated with a depressive phase, although mixed affective states also convey increased risk. All individuals with bipolar disorder should have an up-to-date crisis management plan which outlines the action to be taken should suicidal behaviour emerge. Timely clinical assessment is essential in ensuring that those at high risk are identified. This should include mental state examination, consideration of risk factors, and evaluation of issues such as access to means, preparatory acts before suicide, and also protective factors. While pharmacological approaches are the mainstay of management, less specific measures, such as the removal of access to means, are also important in ensuring safety in the acute situation. Intensifying the clinical support of both patients and relatives, and the sharing of risk information with other health agencies are essential in management. Specific psychological treatments are likely to be helpful in preventing crises, although the evidence base is limited. CONCLUSIONS: The aetiology of suicidal behaviour in bipolar disorder is multifactorial and requires proactive crisis planning and management. A range of issues need to be addressed in the assessment of at-risk patients. Determining the efficacy of interventions specific to reducing suicidality in bipolar disorder should be a research priority.